Refugee Integration between a Rock and a Hard Place: Challenges and Possibilities of Local Integration as a Durable Solution for Eritrean and Somali Refugees in Ethiopia - Mena, Wogene Berhanu (African Human Mobility Review, 2021)
This study examines the challenges and possibilities of local integration forurban refugees by comparing two refugee groups (Eritreans and Somalis) inAddis Ababa. A qualitative research methodology was employed and semistructured interviews with refugees and host communities as well as keyinformant interviews with the Administration of Refugees and Returnees Affairs(ARRA) and local authorities were conducted. In addition, focus groupdiscussions (FGDs) with refugees and host communities of the study areas wereheld. The respondents for both interviews and FGDs were purposively selected.The historical and ongoing relations between Ethiopia and the refugeeproducing countries, a structural factor, impacted not only the country’s policydirection towards the refugees’ but also the refugees’ and hosts’ perceptions oflocal integration. The study revealed that Somali refugees are more integratedin the host communities than Eritrean refugees in the respective areas despitethe cultural compatibility of the latter because of the interplay of structural,refugee and host community related factors.